EFL Student Case Study: WRITING IMPROVEMENT: TRAVELERS’S TALES -TEFL Program Portfolio - Jiménez Arévalo, Fernanda de los Dolores (2012)
The purpose of this study in its first chapter, The EFL Student Case Study, was to improve the writing skills of a specific Second learner student who had an intermedia level of knowledge; by the implementation of four weeks of teaching program. Another aim was to find out the weakness and strengths that she presented with her communicative abilities. Finally, all her class production was evaluated as part of the teachers’ assessment in order to monitor her advance and enhance her second language performance. Moreover, in the second and last chapter of this document, The TEFL Program Portfolio, the main objective was to associate the authors’ production material during this Masters’ program to the TESOL/NCATE STANDARDS FOR THE RECONIZITION OF INITIAL TESOL PROGRAMS IN P-12 ESL TEACHER EDUCATION by the use of some assignments performed during this specialized course. With the interrelation of this TESOL STANDARS and the authors’ documents was confirmed the effectiveness of this Masters’ Program and the authors’ Teaching ESL strategies knowledge obtained.